Consumption-savings decisions under upward looking comparisons: Evidence from Germany, 2002-2011 - Moritz Drechsel-Grau; Kai D. Schmid (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
We demonstrate that interpersonal comparisons lead to keeping up with the Joneses-behavior. Using annual household data from the German Socio-Economic Panel, we estimate the causal effect of changes in reference consumption, defined as the consumption level of all households who are perceived to be richer, on household savings and consumption. When controlling for own income, an increase in reference consumption of 100 euros leads to an increase in consumption of 10 to 25 euros. Upper middle class households are most strongly affected. Our findings provide valuable input for macroeconomic models that consider the economic consequences of interdependent preferences.
Keywords: D11; D12; E21; 330; Household Savings; Household Consumption; Reference Consumption; Interdependent Preferences; Relative Income Hypothesis; Income Inequality